Significant association of Yamamoto-Kohama classification and pathological depth of invasion with cervical lymph node metastasis in early-stage tongue squamous cell carcinoma (Stage I/II) - Wataru Kakuguchi; Yuichi Ashikaga; Aya Yanagawa-Matsuda; Kazuyo Kuribayashi; Saki Shinohara; Naohiro Ogawa; Nako Maishi; Kyoko Hida; Chih-Yuan Fang; Yoichi Ohiro (Elsevier, 2023)
Background/purpose: Tongue squamous cell carcinoma (SCC) has a poor prognosis due to a high rate of cervical lymph node metastasis (CLNM). We aimed to determine clinicopathological features related to the prediction of CLNM in tongue carcinomas (Stage Ⅰ/Ⅱ). Materials and methods: Data from 89 patients with tongue SCC (Stage I/II) were analyzed retrospectively. Patients were treated only with partial glossectomy and not with chemotherapy or radiotherapy until CLNM was observed. No cervical lymph node metastasis survival (NCLNMS) was estimated using the Kaplan-Meier method. The difference in NCLNMS between the groups with and without CLNM was compared using the log-rank test. The Cox regression model was used to estimate hazard ratios and the associated 95% confidence interval. Results: Clinical T2, clinical and pathological depth of invasion (cDOI and pDOI, respectively) > 5 mm, Yamamoto-Kohama (YK)-4c, tumor budding ≥5, worst pattern of invasion −4/5, muscle invasion, perineural invasion, and grade of differentiation 3 were found to be significant CLNM risk factors. Conclusion: CLNM was observed in 25.8% of early-stage tongue carcinomas (Stage I/II). YK-4c and pDOI >5 mm were the most important CLNM risk factors identified. Close follow-up is needed after partial glossectomy when patients with tongue SCC have other risk factors, particularly YK-4c and pDOI >5 mm.